El maltrato infantil y su incidencia en el proceso de enseñanza-aprendizaje, en la educación inicial de los niños y niñas que se encuentran en la modalidad creciendo con nuestros hijos del Ilustre Municipio de Machala- Infa en el sector 10 de septiembre de la cuidad de Machala periodo 2012-2013. - Balcazar Paucar, Iralda Sandra (2013)
The development and application of this research work is based solely to determine the incidence of child abuse resulting in children, causing a truly educational application lens, where teachers are those who in such a situation should be aware of the problem and seek the necessary pedagogically to work with children with these problems strategies.